THE IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION IN EFFORTS TO SHAPE ISLAMIC CHARACTER AND DEVELOP STUDENTS’ TALENTS AND INTERESTS - Ginanjar, Muhammad Hidayat; Rahman, Rahman; Hidayat, Rifqi; Alimul Halim, Ahmad (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The increasing importance of character education, especially in an Islamic context, has prompted a closer look at Islamic Religious Education (PAI) in shaping students' moral values. Purpose: This study examines the implementation of PAI at PESAT High School in Bogor, focusing on its role in shaping students' Islamic character and nurturing their talents and interests. Method: Using a qualitative case study approach, data was collected through observations, interviews, and document analysis. Result: The findings reveal that PAI integrates Islamic values into character formation, promotes ethical conduct, and nurtures students' talents through Islamic-based extracurricular activities. Additionally, PAI influences students' behavior, fostering a stronger commitment to Islamic principles. Conclusion: This research underscores the critical role of structured Islamic education in fostering holistic student development, offering valuable insights for enhancing PAI programs to achieve both religious and academic excellence.